Treatment of Posterior Circulation Fusiform Aneurysms with Flow Diversion vs Stent-Assisted Coiling. (16th November 2020) - Domingo, Ricardo; Tripathi, Shashwat; Perez-Vega, Carlos; Vivas-Buitrago, Tito G.M; Lu, Victor; Todnem, Nathaniel; Quinones-Hinojosa, Alfredo; Tawk, Rabih G
Abstract: INTRODUCTION: Treatment of fusiform aneurysms of the posterior circulation pose a great challenge with unpredictable outcomes due to the absence of a true aneurysm neck and the presence of perforating vessels arising from the lesion and adjacent vessels. METHODS: A systematic search of electronic databases from inception to August 2019 identified 484 articles for screening. After applying inclusion and exclusion criteria, 15 articles were included and data was extracted and analyzed using meta-analysis of proportions. RESULTS: Pooled cohort consisted of 430 aneurysms treated as following: 128 treated with SAC (29.7%) in 5 studies and 302 treated with FD (70.3%) in 11 studies. Complete/Near-Complete occlusion was achieved in 83% overall; with no significant difference between techniques ( P = . 95). Periprocedural complications were observed in 15% overall, with pooled IRs of 18% after FD and 6% after SAC ( P = . 008). Favorable clinical outcome was measured by modified-Rankin-Scale (mRS) score, with pooled IRs after FD and SAC of 83% and 97%, respectively. CONCLUSION: The results of this study suggest similar efficacy in terms of occlusion rate and favorable clinical outcome for posterior circulation fusiform aneurysms treated with SAC and FD. Stroke was the most common complication regardless of the treatment modality and a lower periprocedural complication rate was noted with SAC. Further studies are needed with the primary focus of reducing the risk of stroke with either modality.